Adaptation of the parasitic plant lifecycle: germination is controlled by essential host signaling molecules. Issue 4 (18th December 2020) - Bouwmeester, Harro; Li, Changsheng; Thiombiano, Benjamin; Rahimi, Mehran; Dong, Lemeng
Abstract: Parasitic plants are plants that connect with a haustorium to the vasculature of another, host, plant from which they absorb water, assimilates, and nutrients. Because of this parasitic lifestyle, parasitic plants need to coordinate their lifecycle with that of their host. Parasitic plants have evolved a number of host detection/host response mechanisms of which the germination in response to chemical host signals in one of the major families of parasitic plants, the Orobanchaceae, is a striking example. In this update review, we discuss these germination stimulants. We review the different compound classes that function as germination stimulants, how they are produced, and in which host plants. We discuss why they are reliable signals, how parasitic plants have evolved mechanisms that detect and respond to them, and whether they play a role in host specificity. The advances in the knowledge underlying this signaling relationship between host and parasitic plant have greatly improved our understanding of the evolution of plant parasitism and are facilitating the development of more effective control measures in cases where these parasitic plants have developed into weeds. Abstract : Root parasitic plants grow on the roots of other plants and germinate only in the presence of that host, on which they completely depend, through the perception of host presence signaling molecules called germination stimulants.